PELUANG PELAPORAN KEUANGAN PERUSAHAAN MELALUI INTERNET (Fokus Ekonomi, 2005)
The Development of the internet as a global medium for the dissemination of corporate financial information creates a new reporting environment. Ektensive literature examines the determinant of volountary financial reportingon the internet is an activity that has increased in recent years. This paper explores factors which influence financial disclosure on the internet. The faktors are company size, likuidity, listing status, owner deliberation andleverage level. This type of disclosure is voluntary and unregulated so academiccommunity must be aware of the spreading of financial reporting on the internet.Keywords : Financial Information, internet, company size, liquidity, industri, listing status, sprad on shareholding and leverage level.